2022
DOI: 10.1016/j.cmi.2021.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Seven-versus 14-day course of antibiotics for the treatment of bloodstream infections by Enterobacterales: a randomized, controlled trial

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
58
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(61 citation statements)
references
References 15 publications
2
58
0
1
Order By: Relevance
“…Our results are similar to the recently published study by Molina et al [ 8 ] who also performed a post hoc DOOR analysis of a trial comparing 7 versus 14 days of antibiotics for GNB. In the Molina et al [ 8 ] study, they used Response Adjusted for Duration of Antibiotic Risk (RADAR), a specific version of DOOR, which incorporates the total number of antibiotic days received in the DOOR endpoint (ie, if 2 participants had the same clinical outcome, the participant with the fewest antibiotic days would be given the more desirable rank) [ 9 ]. We did not use RADAR in our study because we chose to focus more directly on the clinical outcomes most impactful to patients rather than duration of antibiotics received, which closely tracked with assigned study arm in this study.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our results are similar to the recently published study by Molina et al [ 8 ] who also performed a post hoc DOOR analysis of a trial comparing 7 versus 14 days of antibiotics for GNB. In the Molina et al [ 8 ] study, they used Response Adjusted for Duration of Antibiotic Risk (RADAR), a specific version of DOOR, which incorporates the total number of antibiotic days received in the DOOR endpoint (ie, if 2 participants had the same clinical outcome, the participant with the fewest antibiotic days would be given the more desirable rank) [ 9 ]. We did not use RADAR in our study because we chose to focus more directly on the clinical outcomes most impactful to patients rather than duration of antibiotics received, which closely tracked with assigned study arm in this study.…”
Section: Discussionsupporting
confidence: 91%
“…There have been 3 published randomized controlled trials (RCTs) assessing antibiotic duration in Gram-negative bacterial bloodstream infection (GNB) [ 6–8 ]. All studies demonstrated noninferiority with a short course (7 days) compared with a conventional course (14 days) of antibiotics with respect to a binary efficacy variable, and one study performed a post hoc desirability of outcome ranking (DOOR) analysis suggesting that a 7-day strategy might be preferred to 14 days [ 8 ]. More comprehensive benefit-to-risk analyses can help continue to elucidate effects of treatment duration on patient outcomes and inform the adoption of a treatment strategy for GNB.…”
mentioning
confidence: 99%
“…These organizations did not participate in the analysis of the study. * Showed data have been summarized from supplementary file 8, included in the original manuscript [4].…”
Section: Conflict Of Interests the Authors Declared No Conflicts Of Interestsmentioning
confidence: 99%
“…Since 2019, three multicentre RCTs with concordant results have established that a 7-day treatment was not inferior to a 10-or 14-day treatment for patients with an uncomplicated GNB BSIs [68][69][70]. We highlight that all patients included in all three RCTs were immunocompetent, afebrile after 3 days of therapy and without uncontrolled infectious sources or prosthetic devices.…”
Section: When and How To Stop Therapymentioning
confidence: 77%